2002
DOI: 10.2527/2002.8082151x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in lipid metabolism induced by recombinant bovine tumor necrosis factor-alpha administration to dairy heifers

Abstract: Endotoxin induces marked changes in lipid metabolism via its effects on cytokines. To evaluate the role of tumor necrosis factor-alpha (TNF) in mediating changes of lipid metabolism in ruminants, we performed a crossover saline-controlled study in Holstein heifers (n = 8; 394.0 kg average BW), investigating the metabolic effects of a single intravenous administration of recombinant bovine TNF (rbTNF, 5.0 microg/kg). Blood samples were taken from a jugular vein at 0 (1100, just before injection), 0.5, 6, 12, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 27 publications
2
33
0
2
Order By: Relevance
“…4A), but the increase was significantly greater throughout the experiment in fattyliver cows. Recent investigations show that administration of TNF-α to experimental animals is associated with decreased appetite and cachexia (von Haehling et al 2002) and increased release of NEFA from adipose tissue into plasma (Kushibiki et al 2002). The BCS of our fatty-liver cows declined immediately after parturition, and their DMI was numerically lower than that of controls during the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…4A), but the increase was significantly greater throughout the experiment in fattyliver cows. Recent investigations show that administration of TNF-α to experimental animals is associated with decreased appetite and cachexia (von Haehling et al 2002) and increased release of NEFA from adipose tissue into plasma (Kushibiki et al 2002). The BCS of our fatty-liver cows declined immediately after parturition, and their DMI was numerically lower than that of controls during the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both investigated APPs correlated positively with non-esterified fatty acids. Recent investigations show that administration of TNFα to experimental animals is associated with decreased appetite and cachexia, and increased release of NEFA from adipose tissue into plasma (Kushibiki et al 2002). Therefore, a higher concentration of NEFA in serum could be related to activation of the immune system.…”
Section: Kinetic Variables Ofmentioning
confidence: 99%
“…Our study showed highly positive correlation between the concentrations of Hp and SAA, as well as between both measured acute phase proteins and the concentrations of NEFA in dairy cows after calving. Kushibiki et al (2002) stated that administration of tumor necrosis factor to dairy cattle, promotes the production of acute phase proteins and is associated with decreased appetite and cachexia, and increased release of NEFA from adipose tissue into the plasma. Therefore, higher concentrations of nonesterified fatty acids in serum could be related to the activation of the immune system.…”
Section: Relationships Between Acute Phase Proteins and Altered Energmentioning
confidence: 99%